2022
DOI: 10.1111/cas.15402
|View full text |Cite
|
Sign up to set email alerts
|

CircPCBP2 promotes the stemness and chemoresistance of DLBCL via targeting miR‐33a/b to disinhibit PD‐L1

Abstract: Diffuse large B‐cell lymphoma (DLBCL) is the most common lymphoid malignancy with a high relapse rate of up to 40%. The prognosis of the disease needs improvement and requires a understanding of its molecular mechanism. We investigated the mechanisms of DLBCL development and its sensitivity to chemotherapy by focusing on circPCBP2/miR‐33a/b/PD‐L1 axis. Human DLBCL specimens and cultured cancer cell lines were used. Features of circPCBP2 were systematically characterized through Sanger sequencing, Actinomycin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It indicated that FKBP3 may contribute to tumour metastasis. Expression of core stemness‐related transcription factors (CD133, SOX2, OCT4) was increased in DLBCL cells 27 . PARK7 was co‐expressed with Nestin during neural stem cells (NSCs) proliferation 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicated that FKBP3 may contribute to tumour metastasis. Expression of core stemness‐related transcription factors (CD133, SOX2, OCT4) was increased in DLBCL cells 27 . PARK7 was co‐expressed with Nestin during neural stem cells (NSCs) proliferation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…25,26 was increased in DLBCL cells. 27 PARK7 was co-expressed with Nestin during neural stem cells (NSCs) proliferation. 28 We found that the stemness of DLBCL cells was enhanced after PARK7 overexpression vector transfection.…”
Section: Discussionmentioning
confidence: 99%
“…In this pathway, circPCBP2 interacts directly with miR-33a/b, while miR-33a/b targets the 3'-UTR of PD-L1. Overall, circPCBP2 promotes the stemness of DLBCL cells but reduces their responsiveness to CHOP treatment by sequestering miR-33a/b , thereby allowing for increased expression of PD-L1 [ 222 ]. Furthermore, the decreased expression of miR-424-5p leads to enhanced drug resistance in DLBCL cells by modulating the PD-1/PD-L1 signaling pathway.…”
Section: Mirna-mediated Regulation Anti-pd-1 and Anti-pd-l1 Treatment...mentioning
confidence: 99%